IMPLEMENTASI MODEL CASE METHOD BERORIENTASI KASUS AUTENTIK UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS TANGGAPAN PADA SISWA KELAS VII.7 SMP NEGERI 7 DENPASAR - Ni Made Wina Kariasih; I Nyoman Adi Susrawan; Ni Nyoman Ardiani (Journal of Innovation Research and Knowledge, 2026)
This research is motivated by the low writing skills in composing response texts among students of class VII.7 at SMP Negeri 7 Denpasar. The main problems identified include students' difficulty in developing arguments, finding main ideas, and formulating logical and structured responses. This study aims to improve students' response text writing skills through the implementation of the Case Method model oriented toward authentic cases. The method used is Classroom Action Research (CAR) conducted in three stages: Pre-Cycle, Cycle I, and Cycle II, referring to the CAR design by Sukidin et al. (2008). Each cycle consists of four stages: planning, implementation, observation and evaluation, and reflection. The research subjects were 40 students of class VII.7 at SMP Negeri 7 Denpasar. Data were collected through performance tests and observation sheets. The results showed significant improvement at each stage. In the Pre-Cycle, the class average was only 58.13 (Poor category) with a 12.5% completion rate. After the intervention in Cycle I, the average increased to 66.88 (Fair category). With further refinement in Cycle II, the class average reached 83.25 (Good category) with a 100% classical completion rate. Thus, the Case Method model oriented toward authentic cases is empirically proven effective in improving students' response text writing skills in an objective, systematic, and logical manner.